Pengetahuan dan Sikap Remaja Putri Difabel tentang Pencegahan Kekerasan Remaja Putri di Kota Bandung - Megawati, Annisa (PLD UIN Sunan Kalijaga, 2021)
UNICEF states that adolescents with disabilities are three or four times more likely to be victims of violence than adolescents in general. This study aims to describe the knowledge and attitudes of young women with disabilities about preventing violence against young women. Based on the case in the city of Bandung, this study uses a descriptive cross-sectional approach. The research sample was all young women with disabilities in the city of Bandung. A total sampling technique brings 72 respondents as the research subjects, where the data collected by interview. The results showed that 45.8% of respondents were in the